Pengaruh Dana Transfer ke Daerah, Tax Ratio, dan Tingkat Pengangguran Terbuka Terhadap Kemiskinan di Pulau Sumatera - Gebby Nabila; Idris (Universitas Negeri Padang, 2026)
This study aims to analyze the effect of transfer funds to regions, tax ratio, and open unemployment rate on poverty in Sumatra Island. The method used is panel data regression. The regression results show that transfer funds to the regions have no significant effect and are positively related to poverty. Meanwhile, the tax ratio and the open unemployment rate have a significant effect and are positively related to poverty. The findings of this study underscore the importance of optimizing the utilization of transfer funds, improving local tax performance, and encouraging sustainable job creation. To reduce poverty in Sumatra Island, local governments need to improve the quality of public spending, broaden the tax base, and strengthen employment policies.